Active Tuning of Optical Constants in the Visible–UV: Praseodymium‐Doped Ceria—a Model Mixed Ionic–Electronic Conductor. Issue 6 (18th January 2021) - Kalaev, Dmitri; Tuller, Harry L.
Abstract: Mixed ionic–electronic conductors offer chemical and electrical means for active tuning of their optical constants, e.g., with variations in oxygen non‐stoichiometry in Pr0.1 Ce0.9 O2– δ, enabling implementation of adaptive thin film optical devices. In situ chemo‐tuning of the extinction coefficient in Pr0.1 Ce0.9 O2– δ at elevated temperatures is demonstrated and a tuning model is provided that treats the interdependence of mobile oxygen vacancies and small polarons coupled to variations in optically active praseodymium ions. Furthermore, a new means for electro‐tuning of the optical constants of mixed ionic–electronic conductors is demonstrated experimentally and modeled for Pr0.1 Ce0.9 O2– δ thin films deposited on grid‐like electrode structures. Modeling of non‐steady‐state optical transmittance modulations in the latter allows for estimation of oxygen vacancy mobility that determines the switching speed of the device. Quenched‐in values of n r and k to room temperature become nonvolatile, providing a modulation range in the extinction coefficient of Δ k  ≈ 0.1 (change of ≈800%) and in the refractive index of Δ n r  ≈ 0.1 (relative to initial n r of ≈2.35). Key figures of merit, including transmission optical modulation of ≈0.04 per 1 mV nm –1, switching energy per area of 1.9 nJ µm –2, and switching times of seconds, are demonstrated, with further improvements possible. Abstract : Active tuning of optical constants in Pr0.1 Ce0.9 O2– δ, a model mixed ionic–electronic conductor, is achieved by control of the valence state of the lanthanide dopant, praseodymium, induced by changes in oxygen stoichiometry driven either by chemical means or by internal redistribution of mobile oxygen vacancies under electrical bias.